Endoluminal radiofrequency ablation with stenting versus stenting alone in patients with malignant biliary obstruction: a meta-analysis of randomized trials - Ramai, Daryl; Maida, Marcello; Smith, Eric R.; Wang, Yichen; Spadaccini, Marco; Previtera, Melissa; Chandan, Saurabh; Huang, Yuting; Tokmak, Salih; Bhandari, Peter; DuBroff, Jason; Ko, Christopher; Morris, John D.; Marasco, Giovanni; Crinó, Stefano Francesco; Facciorusso, Antonio; Mangiavillano, Benedetto; Khashab, Mouen A (Endoscopy, 2024)
Endoluminal radiofrequency ablation (RFA) is a palliative treatment for patients suffering from malignant biliary obstruction (MBO). We aimed to conduct a meta-analysis to evaluate the impact of RFA on stent patency, patient survival, and adverse events.Major databases were searched through December 2023 for patients who had undergone stenting with or without RFA for extrahepatic MBO. A random-effects model was used for analysis, with results expressed as relative risk ratios (RRs) with 95%CIs.Nine RCTs involving 750 subjects with MBO (374 RFA plus stent vs. 376 stent only) were included. Meta-analysis revealed similar risks of stent patency at 3 months (RR 1.01, 95%CI 0.92–1.11; I2 = 4%) for RFA plus stenting vs. stent only. Meta-analysis showed improved survival at 6 months (RR 0.84, 95%CI 0.73–0.96; I2 = 21%; P = 0.01) for RFA plus stenting vs. stent only. Subgroup analysis comparing plastic vs. uncovered metal stents showed that stent patency was unaffected at 3 months (RR 1.06, 95%CI 0.91–1.23; I2 = 17%). Subgroup analysis showed that patients with cholangiocarcinoma experienced an overall survival benefit with RFA plus stenting vs. stenting alone (P < 0.001); however, stent patency remained unaffected (P = 0.08). An increased incidence of cholecystitis was noted with RFA plus stenting vs. stenting alone (5.1% [95%CI 3.1%–7.8%] vs. 0.3% [95%CI 0.01%–1.5%], respectively).Combining endoluminal RFA and stenting may improve overall survival in patients with MBO. RFA did not significantly impact stent patency.